2022
DOI: 10.3390/cells11020198
|View full text |Cite
|
Sign up to set email alerts
|

Correcting Differential Gene Expression Analysis for Cyto—Architectural Alterations in Substantia Nigra of Parkinson’s Disease Patients Reveals Known and Potential Novel Disease—Associated Genes and Pathways

Abstract: Several studies have analyzed gene expression profiles in the substantia nigra to better understand the pathological mechanisms causing Parkinson’s disease (PD). However, the concordance between the identified gene signatures in these individual studies was generally low. This might have been caused by a change in cell type composition as loss of dopaminergic neurons in the substantia nigra pars compacta is a hallmark of PD. Through an extensive meta-analysis of nine previously published microarray studies, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 80 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Second, this review excluded studies that did not report significant ECM-related findings, as per the search criteria. A subsequent exploratory literature search designed to identify omics studies in PD that did not identify ECM-related pathways as top hits resulted in more than 20 studies [ 45 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ]. However, upon closer review of these studies, it was noted that some limited the proteins or pathways that were included in the final models/reports for various reasons and, therefore, may not be expected to find ECM alterations (e.g., removal of genes expressed at low levels [ 112 ], inclusion limited to pathways with established relevance to PD [ 117 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, this review excluded studies that did not report significant ECM-related findings, as per the search criteria. A subsequent exploratory literature search designed to identify omics studies in PD that did not identify ECM-related pathways as top hits resulted in more than 20 studies [ 45 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ]. However, upon closer review of these studies, it was noted that some limited the proteins or pathways that were included in the final models/reports for various reasons and, therefore, may not be expected to find ECM alterations (e.g., removal of genes expressed at low levels [ 112 ], inclusion limited to pathways with established relevance to PD [ 117 ]).…”
Section: Discussionmentioning
confidence: 99%
“…However, upon closer review of these studies, it was noted that some limited the proteins or pathways that were included in the final models/reports for various reasons and, therefore, may not be expected to find ECM alterations (e.g., removal of genes expressed at low levels [ 112 ], inclusion limited to pathways with established relevance to PD [ 117 ]). Several other excluded studies reported significant findings for one or more individual ECM components rather than as part of a gene set [ 45 , 114 , 115 ] or as a significant interaction pathway rather than as part of a primary altered pathway [ 126 ]. Thus, although a substantial number of published omics studies do not report ECM-related pathways as significant, there is still ample reason to suspect their involvement and alteration.…”
Section: Discussionmentioning
confidence: 99%